Recent Publications (Quarterly Journal of Economics, 1962)
Journal Article Recent Publications Get access The Quarterly Journal of Economics, Volume 76, Issue 4, December 1962, Pages 669–673, https://doi.org/10.1093/qje/76.4.669 Published: 01 December 1962